So you qualified as a social worker: Are you ready for this? - Oehlers, Kirsty (Sage Publications, 2017)
This short piece was written as an auto-ethnograpic letter from myself as teacher, to graduating social work students. In this letter, I challenge them to consider the learning that will come from the feelings and thoughts evoked by the social work journey ahead.